Analisis Penamaan tempat Wisata di Kota Semarang Terhadap Identitas Lokal dan Nilai Budaya - Maulana Febryan Saputra; Imam Baehaqie; Auliya Eka Wijayatri (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Language reflects the culture and identity of a community, including in the naming of places that hold historical and social value. This study aims to describe the meaning, cultural value, and local identity in the naming of tourist attractions in the multicultural city of Semarang. Using a qualitative descriptive method with a narrative approach in line with interviews and online data searches, this study analyzes names such as Lawang Sewu, Sam Poo Kong, Kota Lama, Blenduk Church, Kauman Mosque, and Ronggowarsito Museum based on their lexical and associative meanings. The results show that place naming not only functions as a geographical marker but also reflects the history, cultural acculturation, and local wisdom of the people of Semarang. Thus, place naming in Semarang becomes a symbol of the integration of language, culture, and local identity that shapes the city's unique character.